Who wants violence? The political economy of conflict and state building in Colombia (2017)
Enduring violent conflict is the flip side of the coin of a weak state. In this article, I propose some political economy underpinnings for the persistence of conflict (and the weak state). Focusing on the case of Colombia, I discuss three broad sets of mechanisms that are also relevant elsewhere. First, a "public goods trap" implies that allow supply of public goods (including security and order) produces a low demand for public goods, and vice versa. This trap is grounded on, and reproduces, political and economic inequality. Second, conflict and a weak state create economic and political rents, producing vested interests in the status quo. I argue that political rents are a particularly strong obstacle, partly because reformers face a sort of curse of dimensionality: many things have to work well for state capacity and stable peace to consolidate. Politically powerful groups take advantage of any weak spot to defend their rents, producing countervailing negative effects following state building efforts. Finally, the very clientelistic pattern of political exchange in many societies consolidates a weak state, and weak states are fertile ground for clientelism to flourish. This vicious circle of clientelism and state weakness is another reason for persistence. I conclude discussing some lessons for reformers, though the very nature of the argument implies that there are no easy recipes for success.